Block Bone Graft Fixation ( Onlay): A Modification of the Surgical Technique - Gealh, Walter Cristiano [UNESP]; Santos, Pamela Leticia dos; Silva Pereira, Cassiano Costa [UNESP]; Okamoto, Tetuo; Silva, Cristina Antoniali [UNESP]; Okamoto, Roberta [UNESP] (Lippincott Williams & Wilkins, 2014)
Several reconstructive methods of the alveolar ridge have been reported to make possible future rehabilitations with implants. Many of these methods come from studies done in animals, mainly rats. With this clinical practice based on scientific evidence, any experimental procedure that can be undertaken in real life is fundamental. Thus, any research that emulates as closely as possible those techniques used in humans are important. This study describes the modification of the technique for block bone graft fixation (onlay) in rats using the lag screw-type technique, normally used in clinical procedures for grafts in humans. The conclusion was that the execution of the described procedures minimizes interference of blood flow in the area because of the maintenance of the muscle insertion in the buckle aspect of the most anterior region of the mandible, providing better stability to the graft and better contact interface of the graft and receptor bed.
Keywords: Bone graft; onlay bone grafts; rats; surgical technique